NK Cells in the Tumor Microenvironment as New Potential Players Mediating Chemotherapy Effects in Metastatic Melanoma - Garofalo, Cinzia; De Marco, Carmela; Cristiani, Costanza Maria (Frontiers in Oncology, 2021)
Until the last decade, chemotherapy was the standard treatment for metastatic cutaneous melanoma, even with poor results. The introduction of immune checkpoints inhibitors (ICIs) radically changed the outcome, increasing 5-year survival from 5% to 60%. However, there is still a large portion of unresponsive patients that would need further therapies. NK cells are skin-resident innate cytotoxic lymphocytes that recognize and kill virus-infected as well as cancer cells thanks to a balance between inhibitory and activating signals delivered by surface molecules expressed by the target. Since NK cells are equipped with cytotoxic machinery but lack of antigen restriction and needing to be primed, they are nowadays gaining attention as an alternative to T cells to be exploited in immunotherapy. However, their usage suffers of the same limitations reported for T cells, that is the loss of immunogenicity by target cells and the difficulty to penetrate and be activated in the suppressive tumor microenvironment (TME). Several evidence showed that chemotherapy used in metastatic melanoma therapy possess immunomodulatory properties that may restore NK cells functions within TME. Here, we will discuss the capability of such chemotherapeutics to: i) up-regulate melanoma cells susceptibility to NK cell-mediated killing, ii) promote NK cells infiltration within TME, iii) target other immune cell subsets that affect NK cells activities. Alongside traditional systemic melanoma chemotherapy, a new pharmacological strategy based on nanocarriers loaded with chemotherapeutics is developing. The use of nanotechnologies represents a very promising approach to improve drug tolerability and effectiveness thanks to the targeted delivery of the therapeutic molecules. Here, we will also discuss the recent developments in using nanocarriers to deliver anti-cancer drugs within the melanoma microenvironment in order to improve chemotherapeutics effects. Overall, we highlight the possibility to use standard chemotherapeutics, possibly delivered by nanosystems, to enhance NK cells anti-tumor cytotoxicity. Combined with immunotherapies targeting NK cells, this may represent a valuable alternative approach to treat those patients that do not respond to current ICIs.